Power regulation by couple half wave LPWM rectifier at three-phase loads - Can, Erol (Array, 2019)
The paper presents an application of power control by couple half wave LPWM rectifiers processing at the energy distribution line. The switching method with the components of semiconductor for alternating energy control in the energy distribution line is used on alternating energy sources. In three-phase power line and load, power control and regulation are done with the proposed modulation correction index (MCI). Therefore, the simulation model of 3-phase energy distribution is established after the relationships between the energy sources and the circuit elements are determined by the circuit analysis method. The controls of the current and the voltage are done by trying at the different loads in the line at the simulation. According to the modulation correction index (MCI), currents of unbalanced loads are balanced by the proposed method on the power line. Then, the balance currents and powers that MCI provides are calculated. Finally, a power line of 15 km at length that is created by connecting the model of RLC is tested. Obtained results show the effectiveness of the proposed method.